POLÍTICAS PÚBLICAS DE INCENTIVO À LEITURA: UM ESTUDO DO PROJETO “LITERATURA EM MINHA CASA” PONTA GROSSA 2007 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
This research analyzed the government project of incentive for reading "Literatura em Minha Casa", linked to the Programa Nacional Biblioteca da Escola (PNBE), with resources from the Fundo Nacional de Desenvolvimento da Educação (FNDE), organ of Ministry of Education and Culture (MEC). The research had the concern in establishing the relationships between what the project proposed and what they executed in practice. The authors that sustained the theoretical discussions were: Freire (1982); Perrotti (1990); Chartier (1990), (1996), (1999), (2001); Silva (1983), (1986), (1991), (1995); Cavallo and Chartier (1998), (1999); Febvre and Martin (1992); Melo (2003), Britto (2003); Andrade (2004) and Suassuna (1998). The documentary analysis focused the objectives, the target public, the criteria for the distribution of the books, the financial investments, the basic conceptions and the actions that orientated the implantation and the implementation of the project "Literatura em Minha Casa” in the schools. The contents of the interviews with the managers, the educators, the teachers and the responsible ones for the libraries of the municipal and state schools of the city of Ponta Grossa, Paraná, were analyzed. From the analysis of the emanated documents of MEC, we observed that the referred project had as initial goal to turn accessible to the students of 4th, 5th and 8th grades of the Elementary School and to their families a group of literary texts. The main conclusions are: a) the majority of the school managers ignored the programs, the projects and the incentive campaigns for reading that emanated from the Federal Government; b) the books did not get at schools in the way how it was proposed in the official documents from the governmental organs; c) the students did not receive the kits as prescribed in the project; d) in some schools, as in the state as in the municipal ones, there is a residue of volumes in the shelves of the libraries and in the reading rooms and; e) the schools received a very short amount of kits for the demand of registrations. According to the information from the citizen, we verified some distance between the intentions manifested in the documents and the results of the proposal implemented in the schools. The project was not able to get the visibility neither inside of the schools, nor in the community.
Keywords: políticas públicas; política de leitura; programa; projetos e campanhas de leitura e formação de leitores; public politics; reading politics; program; projects and reading campaigns and formation of readers; CNPQ::CIENCIAS HUMANAS::EDUCACAO